2011
DOI: 10.3144/expresspolymlett.2011.67
|View full text |Cite
|
Sign up to set email alerts
|

Time and temperature effects on Poisson’s ratio of poly(butylene terephthalate)

Abstract: Abstract. The viscoelastic nature of the Poisson's ratio of a semicrystalline poly (butylene terephthalate) is highlighted by investigating its dependence on time, temperature and strain rate, under two types of loading conditions: i) constant deformation rate tests, in which the transverse strain is measured in tensile ramps at various temperatures and at two strain rates; and ii) constant deformation tests, in which, under a constant axial deformation, the transverse strain is measured as a function of time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…Because this value is representative of values for glassy polymers [43], it is uncertain how much agreement can be improved by increasing m. In any event it is likely that increasing m will require changes in the relaxation model for deviatoric stresses as the relaxation of these stresses plays a major role in the determination of the transverse velocity-time profiles. Quantitative agreement with longitudinal wave arrivals is excellent over the full range of pressures (i.e., up to 18 GPa) used for reverberation experiments on thick samples.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Because this value is representative of values for glassy polymers [43], it is uncertain how much agreement can be improved by increasing m. In any event it is likely that increasing m will require changes in the relaxation model for deviatoric stresses as the relaxation of these stresses plays a major role in the determination of the transverse velocity-time profiles. Quantitative agreement with longitudinal wave arrivals is excellent over the full range of pressures (i.e., up to 18 GPa) used for reverberation experiments on thick samples.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…• Material parameters are taken from the literature [13,14], and the void space is assume to have 1:1000 of the solid modulus with Poisson's ratio 0.33.…”
Section: Mechanical Calculationsmentioning
confidence: 99%
“…1 For this study, the PMC infill panel uses two types of closed-cell polymeric foam for the cores, which are Polyurethane (PU) and Polybutylene terephthalate (PBT). Tobushi [5] and Padini [7] have shown that the increase of temperature causes the reduction of characteristic parameter, such as elastic modulus, yield stress and Poisson's ratio of the polymer material, thus affects those of the polymeric foam. Gibson and Ashby [2] derived the prediction of relative Young's Modulus as function of relative density of foam as shown in equation (1) below:…”
Section: Configuration Of Pmc Infill Wall and Effect Of Temperaturementioning
confidence: 99%